2018
DOI: 10.1002/asia.201800815
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Silver Nanoparticles in an Amine‐Functionalized Porphyrin Metal–Organic Framework and Its Use as a Heterogeneous Catalyst for CO2 Fixation under Atmospheric Pressure

Abstract: A new porphyrin-based compound, [Zn (C H N )(C H N O ) (DEF) ](DEF) (1; DEF=N,N-diethylformamide), has been synthesized by employing 5,10,15,20-tetrakis(4-pyridyl)porphyrin, 1,2-diamino-3,6-bis(4-carboxyphenyl)benzene, and Zn salt at 100 °C under solvothermal conditions. The structure, as determined by single-crystal XRD studies, is three-dimensional with threefold interpenetration. The usefulness of free -NH groups in the ligand was exploited for anchoring silver nanoparticles through a simple solution-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…On the basis of the experimental results, DFT calculations and previous reports, a plausible reaction mechanism for the carboxylative coupling reaction is proposed in Scheme . Firstly, Ag nanoparticles of Ag/M−CeO 2 can coordinate terminal alkynes with Cs 2 CO 3 to form silver acetylide intermediate A .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the basis of the experimental results, DFT calculations and previous reports, a plausible reaction mechanism for the carboxylative coupling reaction is proposed in Scheme . Firstly, Ag nanoparticles of Ag/M−CeO 2 can coordinate terminal alkynes with Cs 2 CO 3 to form silver acetylide intermediate A .…”
Section: Resultsmentioning
confidence: 95%
“…In the effort to develop sustainable processes, a few heterogeneous catalysts have been introduced in this reaction. For instance, CuBr loaded on activated carbon, CuCl 2 incorporated in polyvinyl imidazolium tri‐cationic ionic liquid, Cu nanoparticles supported on Al 2 O 3 , and Ag nanoparticles encapsulated in the porphyrin MOF displayed excellent catalytic activities for the carboxylative coupling reaction. However, due to the thermodynamic and kinetic stability of CO 2 , the transformation of CO 2 to functionalized 2‐alkynoates using heterogeneous catalysts under mild reaction condition remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra appeared in Figure , was a drop in stretching frequency for the N peak upon nanoparticle grafting, while all the other peaks remain almost unchanged. The coordination interaction within the nanocatalyst is favoured between N site of the chelating type polymer ligand and Ag NPs which may promote the suitable binding of Ag NPs on the HMP‐2 polymer surface …”
Section: Resultsmentioning
confidence: 99%
“…The experimental results showed that the optimized Ag 2 O@Uio-66 composite exhibited a high chemical absorption rate of 1 ppm for H 2 S at room temperature. Gargi Dutta et al, [23] studied the application of silver nanoparticles encapsulation in aminogenatedporphyrin MOFs as co-stationary polyphase catalysts under atmospheric pressure. Silver nanoparticles were anchored to MOFs by simple solution method, and carboxylation catalytic activity of terminal alkynes was studied by inverting phase atmospheric pressure method.…”
Section: Introductionmentioning
confidence: 99%